Pengembangan E-Modul Untuk Pembelajaran Nail Art Pada Siswa Student Day SMA Plus PGRI Cibinong - Lia Aprilia; Mari Okatini Armandari; Titin Supiani (Journal on Education, 2025)
This study aims to develop an E-Module as learning media for nail art for grade X and grade XI of SMA Plus PGRI Cibinong in “Student Day” learning activity. The background of this study is the limitations of the previously-existing learning media that were less interactive and did not support independent learning. The research method used is Research and Development with the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). Product validation was carried out through a feasibility test by material experts and media experts. The results of the validation of material experts in stage 1 were 89.01% and stage 2 were 93.33%. The results of the validation of media experts in stage 1 were 89.33% and stage 2 were 96%. Then, the researcher also conducted practicality test for the chosen students as the representatives of grade X and grade XI as many as 37 students out of 55 students in total that was carried out in two stages, namely a small group test (10 students) with a result of 92.7% and a field test (27 students) with a result of 97.2%. The results of the study indicate that this E-Module has been valid, feasible and practical to use as a learning medium.